Family History of Hypertension and Echocardiographic Left Ventricular Hypertrophy in Hypertensive Nigerians - Olugbenga Olusola Abiodun; Tina Anya; Victor Tunde Adekanmbi; Dike Ojji (Wiley, 2024)
Introduction. Studies on the relationship between a family history of hypertension and left ventricular hypertrophy are sparse. We evaluated this relationship in patients with essential hypertension. Methods. A total of 1668 patients with essential hypertension were consecutively enrolled in the prospective Federal Medical Centre Abuja Hypertension Registry. First-degree family history was defined by the presence of a known history of hypertension in any or both parents, siblings, and children. Echocardiographic left ventricular hypertrophy was diagnosed using the criteria of the American Society of Echocardiography and the European Association of Cardiovascular Imaging. Results. The prevalence of a family history of hypertension, echocardiographic, and electrocardiographic left ventricular hypertrophy were 61.7%, 46.8%, and 30.8%, respectively. After multivariable adjustment, paternal history of hypertension [OR: 1.56, CI: 1.20-2.05, p=0.001] was associated with an increased risk of echocardiographic left ventricular hypertrophy, while maternal history of hypertension [OR: 0.72, CI 0.58-0.91, p=0.006] was associated with a reduced risk. Age ≥50 years (p=0.026), duration of hypertension ≥1 year (p=0.047), and heart failure (p<0.001) were associated with an increased risk of left ventricular hypertrophy, while male sex (p<0.001) was associated with a reduced risk. Conclusion. Our study showed that a paternal history of hypertension is associated with an increased left ventricular hypertrophy risk among patients with essential hypertension, while maternal history is protective.